Bituin the distance a multimodal campaign that aims to bridge the communication gap betweeen parenting Overseas Filipino Workers (OFW) and their left-at-home children aged 7 to 11 years old - Banday, Rafael Joy F.
After the Martial Law, Marcos administration saw itself plagued with the ballooning unemployment rate because the domestic economy could not generate enough sustainable local jobs. Because of this, the migration of Filipino workers was seen as a temporary solution to the country's increasing foreign debt during the late 90s. Republic Act 8042, most commonly known as the Migrant Workers and Overseas Filipinos Act of 1995 provided the institution the policies of overseas employment and established a higher standard of protection and promotion of the welfare of migrant workers, their families and overseas Filipinos.